High-throughput sequencing reveals circular substrates for an archaeal RNA ligase. Issue 8 (3rd August 2017) - Becker, Hubert F.; Héliou, Alice; Djaout, Kamel; Lestini, Roxane; Regnier, Mireille; Myllykallio, Hannu
ABSTRACT: It is only recently that the abundant presence of circular RNAs (circRNAs) in all kingdoms of Life, including the hyperthermophilic archaeon Pyrococcus abyssi, has emerged. This led us to investigate the physiologic significance of a previously observed weak intramolecular ligation activity of Pab 1020 RNA ligase. Here we demonstrate that this enzyme, despite sharing significant sequence similarity with DNA ligases, is indeed an RNA-specific polynucleotide ligase efficiently acting on physiologically significant substrates. Using a combination of RNA immunoprecipitation assays and RNA-seq, our genome-wide studies revealed 133 individual circRNA loci in P. abyssi . The large majority of these loci interacted with Pab 1020 in cells and circularization of selected C/D Box and 5S rRNA transcripts was confirmed biochemically. Altogether these studies revealed that Pab 1020 is required for RNA circularization. Our results further suggest the functional speciation of an ancestral NTase domain and/or DNA ligase toward RNA ligase activity and prompt for further characterization of the widespread functions of circular RNAs in prokaryotes. Detailed insight into the cellular substrates of Pab 1020 may facilitate the development of new biotechnological applications e.g. in ligation of preadenylated adaptors to RNA molecules.